Development of an Academic Well-being Model for Gifted Students: A Grounded Theory Study - Sarami, Paria; Nejatifar, Sara; Aghaziarati, Ali (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2024)
Objective: This study aimed to identify the factors influencing the academic well-being of gifted students to develop a model.Methods and Materials: The research method used in this study was qualitative, utilizing a grounded theory approach. Data were collected through semi-structured interviews. The data were examined and analyzed based on Strauss and Corbin's (1998) grounded theory methodology. The study population consisted of all male and female gifted sixth-grade students in the city of Isfahan in 2022. The research sample was selected through purposive sampling, and after conducting interviews with 23 students, the factors influencing academic well-being were identified. It should be noted that data analysis was conducted using three stages of open, axial, and selective coding.Findings: Based on the results of the study, open codes were organized around 57 concepts, axial codes included 8 concepts, and selective codes were identified and extracted into 4 concepts under the titles of school context, family context, social context, and individual resources.Conclusion: The findings of the research suggest that by recognizing and understanding the factors influencing academic well-being, it is possible to create conditions that enhance the academic well-being of gifted students.